Ecomorphology of crabs and swimming crabs (Crustacea DecapodaBrachyura) from coastal ecosystems (Brazilian Journal of Oceanography, 2016)
Brachyuran crabs are one of the most diverse taxa of crustaceans, occurring in almost all coastal habitats. Due to their high morphological diversification, the authors sought to ascertain the existence of morphological patterns related to the habitat of coastal brachyuran crabs. We analyzed 17 species from mangrove forests, rocky shores, sandy beaches and exclusively aquatic marine/estuarine ecosystems. A total of 16 linear measurements of males and 17 of females were obtained for each habitat. We were able to discriminate three functional groups of crab species, based on their habitat: 1. Complex Substrates, 2. Semiterrestrial, 3. Exclusively Aquatic. The species belonging to the Complex Substrates group had long ambulatory legs, as well as being heteroquely related to uneven terrain. Semiterrestrial species showed ambulatory legs of different sizes, allowing them to walk easily on the terrestrial terrain due to the long fourth ambulatory leg, and long eyestalks which are important for visual communication. Exclusively Aquatic species showed the largest carapace widths and the shortest eyestalks. The presence of different crab lineages in the environments analyzed allows us to demonstrate the clear evolutionary convergence, by which the crabs adapted to their specific habitat and environment.